2011
DOI: 10.1007/s00114-011-0870-4
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic analysis of the alarm call of the Anatolian ground squirrel Spermophilus xanthoprymnus: a description and comparison with alarm calls of the Taurus S. taurensis and European S. citellus ground squirrels

Abstract: The Anatolian ground squirrel Spermophilus xanthoprymnus like other ground-dwelling sciurids, emits alarm calls in the presence of predators. In this study, we provide a description of the acoustic structure of alarm call of this species and compare it to those of two closely related species, the Taurus ground squirrel Spermophilus taurensis and the European ground squirrel Spermophilus citellus. The alarm call of S. xanthoprymnus is a tonal sound mostly consisting of two different elements-the first element h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
1
9
0
2
Order By: Relevance
“…When male and female calls were reported, we focused on male calls (the same criteria was adopted for body mass). However, previous studies have reported very little or a total absence of sexrelated variation in the structure of alarm call notes (Miller & Engstrom, 2007;Matrosova et al, 2011;Schneiderov a & Policht, 2012). This is not entirely unexpected given that many rodents are typically monomorphic or exhibit slight sexual size dimorphism (Schulte-Hostedde, 2007;Lu, Zhou & Liao, 2014).…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…When male and female calls were reported, we focused on male calls (the same criteria was adopted for body mass). However, previous studies have reported very little or a total absence of sexrelated variation in the structure of alarm call notes (Miller & Engstrom, 2007;Matrosova et al, 2011;Schneiderov a & Policht, 2012). This is not entirely unexpected given that many rodents are typically monomorphic or exhibit slight sexual size dimorphism (Schulte-Hostedde, 2007;Lu, Zhou & Liao, 2014).…”
Section: Methodsmentioning
confidence: 88%
“…However, previous studies have reported very little or a total absence of sexrelated variation in the structure of alarm call notes (Miller & Engstrom, 2007;Matrosova et al, 2011;Schneiderov a & Policht, 2012). Most information originates from studies published in specialized journals (Bioacoustics, Journal of the Acoustical Society of America) and species reviews (http://www.science.smith.edu/ departments/Biology/VHAYSSEN/msi).…”
Section: Methodsmentioning
confidence: 99%
“…Compared to S. xanthoprymnus (see Gür and Gür 2010), diagnostic characters for S. citellus are as follows: the skull is less angular, back indistinctly spotted, and tail longer (S. xanthoprymnus, range: 30-72 mm; S. citellus, range: 31-90 mm) with black hairs dorsally Vohralík 2005, 2012). S. citellus, S. taurensis, and S. xanthoprymnus can be clearly distinguished on the basis of their alarm calls (Schneiderova´and Policht 2011a, 2011b.…”
Section: Diagnosismentioning
confidence: 99%
“…1). Наличие двух компонентов ранее было обнаружено в сигнале шести из 15 видов сусликов Евразии [3][4][5].…”
unclassified
“…Благодарности. Это исследование инициировано публикациями Ирены Шнайдеровой [5,8,12], за что автор выражает ей свою глубокую и искреннюю благодарность.…”
unclassified